Characterization of Spatial Variability of Soil Physical Properties at UTP Campus - Mohd Faiz Fahmi Bin Abu Bakar, Mohd Faiz Fahmi (Universiti Teknologi Petronas, 2010)
Characterization of Spatial Variability of Soil Physical Properties at UTP Campus